Neurological Complications in Tsutsugamushi Disease (Scrub Typhus) from Northeastern Region of India - Sharma, S. R.; Masaraf, H.; Lynrah, K. G.; Lyngdoh, M. (Current Overview on Disease and Health Research Vol. 5, 2022)
The goal of this study was to characterize neurological complications in scrub typhus from northeastern region of India. We conducted a prospective study of scrub meningoencephalitis at North Eastern Indira Gandhi Regional Institute of Medical Sciences among patients admitted to hospital between October 2009 and November 2011. The clinical pictures of scrub typhus are typically associated with fever, rash, myalgia, and diffuse lymphadenopathy. The diagnosis was made based on the clinical pictures, presence of an eschar, and a positive Weil–Felix test (WFT) with a titer of >1:160 and if required a positive scrub IgM enzyme-linked immunosorbent assay. Lumbar puncture was carried out on patients with headache, nuchal rigidity, altered sensorium, or cranial nerve deficits, and magnetic resonance imaging (MRI) brain was performed if necessary. The study included 23 patients with scrub typhus meningitis who were serologically confirmed. There were 13 men and 10 women. Fever \(\ge\)1 week was the most common manifestation (39.1%). Surprisingly, none of them had an eschar. Median cerebrospinal fluid (CSF) cell count, lymphocyte percentage, CSF protein, CSF glucose/blood glucose, CSF ADA were 17 cells/\(\mu\)L, 90%, 86 mg/dL, 0.6605 and 3.6 U/mL, respectively. Doxycycline was administered to all patients. In our study, there was no death. Scrub typhus cannot be ruled out in the absence of Eschar. Because clinical features and CSF findings can be mistaken for tuberculous meningitis, misdiagnosis may result in unnecessary long-term empirical antituberculous therapy in cases of lymphocytic meningoencephalitis. Delays in treatment have the potential to be fatal. In resource-poor countries, WFT remains a useful and affordable diagnostic tool for this disease.